2019
DOI: 10.1093/mnras/stz1584
|View full text |Cite
|
Sign up to set email alerts
|

The period–luminosity relation of red supergiants with Gaia DR2

Abstract: We revisit the K -band period-luminosity (P-L) relations of Galactic red supergiants using Gaia Data Release 2 parallaxes and up to 70 yr of photometry from AAVSO and ASAS campaigns. In addition, we examine 206 LMC red supergiants using 50 yr of photometric data from the Digitised Harvard Astronomical Plate Collection. We identified periods by computing power spectra and calculated the period-luminosity relations of our samples and compared them with the literature. Newly available data tighten the P-L relatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 63 publications
8
47
0
Order By: Relevance
“…For clarity, tracks with an initial mass that is intermediate between these two values have been omitted. similar agreement was found with the PLDs presented by Chatys et al (2019) for galactic and LMC red supergiants.…”
Section: Pulsation Mode Of High-mass Lpvssupporting
confidence: 91%
See 2 more Smart Citations
“…For clarity, tracks with an initial mass that is intermediate between these two values have been omitted. similar agreement was found with the PLDs presented by Chatys et al (2019) for galactic and LMC red supergiants.…”
Section: Pulsation Mode Of High-mass Lpvssupporting
confidence: 91%
“…A parallel sequence shifted towards shorter periods, which is seen in our study (Fig. 19), in the paper by Ren et al (2019) and in the work by Chatys et al (2019), is likely formed by first overtone pulsators among the massive AGB stars and the supergiants.…”
Section: Pulsation Mode Of High-mass Lpvssupporting
confidence: 85%
See 1 more Smart Citation
“…Kiss et al (2006) and Percy & Khatu (2014) identified periods of a few hundred to a few thousand days with varying stellar lightcurve morphology for RSGs in the AAVSO International Database. Such pulsations have also been observed occurring in RSGs within the Small and Large Magellanic Clouds (Feast et al 1980;Ita et al 2004;Szczygie l et al 2010;Yang & Jiang 2011;Yang & Jiang 2012;Yang et al 2018), M31 and M33 (Soraisam et al 2018;Ren et al 2019), M51 (Conroy et al 2018), M101 (Jurcevic et al 2000), within HST archival data of NGC 1326A, NGC 1425, and NGC 4548 (Spetsieri et al 2019), and within the GAIA DR2 RSG sample (Chatys et al 2019). These works identify these RSG pulsations Corresponding author: J.…”
Section: Introductionmentioning
confidence: 63%
“…Critically, the brightness of Betelgeuse varies in a systematic way on at least two different timescales, and these periodicities were measured with good precision by Kiss et al (2006) (and later corroborated by Chatys et al 2019). The shorter occurs with a period of ∼388 days and the longer with a period of ∼5.6 yr (2050 days).…”
mentioning
confidence: 79%